INTERNATIONAL EXPERIENCE IN THE FIELD OF STRATEGIC RISK MANAGEMENT OF AGRI-FOOD ENTERPRISES - HOLOVKO, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2021)
At the current stage of enterprise development, an effectively planned management system plays a key role. Any changes in management approaches lead to significant conceptual transformations. For Ukrainian agricultural enterprises operating in conditions of fierce competition and a dynamic external environment, it is vital to implement innovative methods to ensure sustainable development. The article is devoted to studying international experience in strategic risk management of agri-food enterprises and identifying methods that can be applied in Ukrainian realities. Effective risk management systems are an integral part of sustainable enterprise development. Modern agribusiness challenges, such as climate change, instability of raw material prices, global economic crises, and trade restrictions, require an integrated approach to risk management. Developed countries have accumulated significant experience in creating and implementing effective risk management strategies, which can be useful for Ukrainian enterprises. It has been determined that one of the most important elements of international practice is the implementation of risk management standards (for example, ISO 31000 standards, which provide clear recommendations for creating a comprehensive risk management system that minimizes the consequences of adverse events and increases the efficiency of operational activities). It has been proven that effective strategic risk management in the agri-food sector is based on several key factors: modern technologies, standardized approaches to risk management, insurance mechanisms and state support. Ukrainian agricultural enterprises should adapt these practices to increase their resilience to external challenges and ensure sustainable development in conditions of fierce competition.